2014
DOI: 10.1111/ceo.12391
|View full text |Cite
|
Sign up to set email alerts
|

Value of whole exome sequencing for syndromic retinal dystrophy diagnosis in young patients

Abstract: Background: Several retinal dystrophies are associated with syndromic features including such conditions as Bardet-Biedl and Joubert syndromes. Cohen syndrome is an autosomal recessive disorder associated with multiple clinical manifestations including developmental delay, acquired microcephaly, myopia, pigmentary retinopathy, joint hypermobility, truncal obesity, friendly disposition and intermittent neutropenia. In young patients, diagnosis is difficult, because several of the characteristic features may not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In fact, a pattern of agalactosylated and asialo‐fucosylated structures, indicative of a N‐glycan maturation defect, was found in serum proteins of these patients . Intermittent congenital neutropenia is a hallmark of this disease (detected in 168/224 VPS13B‐CDG patients) . One patient had leukopenia without neutropenia while another had pancytopenia .…”
Section: The Immunological Impact Of Glycosylation Defects—an Update mentioning
confidence: 94%
“…In fact, a pattern of agalactosylated and asialo‐fucosylated structures, indicative of a N‐glycan maturation defect, was found in serum proteins of these patients . Intermittent congenital neutropenia is a hallmark of this disease (detected in 168/224 VPS13B‐CDG patients) . One patient had leukopenia without neutropenia while another had pancytopenia .…”
Section: The Immunological Impact Of Glycosylation Defects—an Update mentioning
confidence: 94%
“…In a third family of Lebanese origin, whole exome sequencing revealed a 1 bp deletion (c.11327delA) leading to a frameshift mutation in VPS13B in two affected siblings. The 7‐year‐old girl and her 4‐year‐old brother presented with developmental delay, postnatal onset microcephaly, characteristic facial gestalt, and pigmentary retinopathy (Prokudin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finnish Mediterranean (Bugiani et al, 2008;Douzgou & Petersen, 2011) Amish (Falk et al, 2004) Irish travelers (Murphy, Flanagan, Dunne, & Lynch, 2007) Our patient to a frameshift mutation in VPS13B in two affected siblings. The 7-yearold girl and her 4-year-old brother presented with developmental delay, postnatal onset microcephaly, characteristic facial gestalt, and pigmentary retinopathy (Prokudin et al, 2015).…”
Section: T a B L E 1 Different Genotypes And Associated Clinical Phenmentioning
confidence: 99%
“…However, difficulty in distinguishing between causal and coincidental obesity in unique cases necessitates replication of these results in additional patients. WES has also discovered novel mutations and/or structural variants for syndromic obesity in previously implicated genes and revealed clinical heterogeneity in several obesity syndromes . For example, in a study of individuals with atypical Alström syndrome, novel ALMS1 mutations were identified using WES secondary to a negative classical genetic test of ALMS1 mutational hotspots .…”
Section: Established Strategiesmentioning
confidence: 99%